The Effects of Intrathecal Bupivacaine-Fentanyl and Bupivacaine-Morphine on Ephedrine Requirements and Health Status of Fetus in Elective Cesarean Section. (Annals of Medical Research, 2021)
None
Keywords: Cesarean section, Bupivacaine, Fentanyl, Morphine, Efedrine